Validation Data Stock Opname Persediaan Berbasis Komputerisasi Untuk Penjualan - Mubarok, Husni; Lukman, Afit Muhammad; Hellyana, Corie Mei; Agustyaningrum, Cucu Ika (Lembaga Dongan Dosen, 2025)
The Tri Dharma of higher education must be fulfilled, including community service which aims to improve the standard of living of the community around the campus domicile. The students of the Riyadush Solihin Islamic boarding school whose learning is focused on religion, feel it is necessary to provide provisions to enrich their scientific knowledge regarding validation of stock taking data for inventory for sales. The analysis method for primary and secondary data uses a descriptive style combining quantitative and qualitative to interpret the characteristics of students towards training. The final results of the training achievements of the 26 respondents were phenomenal. The students were very enthusiastic about learning to validate data on stock taking, inventory for sales, which could add to their scientific knowledge, with an average initial test of 70.77%, the predicate was more than sufficient, which was seen to increase, changing to a final test of 93. .08 very good predicate. Training activities provide benefits with an average score of 4.42% grade A (strongly agree), increase insight with an average score of 4.27% grade A (strongly agree), increase skills with an average score of 4.23% grade A (strongly agree). providing the use of science and technology with an average score of 4.42% grade A (strongly agree), providing solutions to problems with an average score of 4.04% grade A (strongly agree).